Comparative transcriptome analysis reveals regulators mediating breast muscle growth and development in three chicken breeds. Issue 3 (3rd July 2019) - Zhang, Zengrong; Du, Huarui; Yang, Chaowu; Li, Qingyun; Qiu, Mohan; Song, Xiaoyan; Yu, Chunlin; Jiang, Xiaoyu; Liu, Lan; Hu, Chenming; Xia, Bo; Xiong, Xia; et al.
Abstract: Objective: The goal of this study was to investigate the mechanisms of muscle growth and development of three chicken breeds. Participants: Eighteen chickens, including three different breeds with different growth speeds (White Broiler, Daheng, and Commercial Layers of Roman), were used. Methods: Total RNA from breast muscle of these chickens was subjected to a gene expression microarray. Differentially expressed genes (DEGs) were screened and functional enrichment analysis was performed using DAVID. Seven DEGs were confirmed by quantitative reverse transcription PCR. Results: Overall, 8, 398 DEGs were found among the different lines. The DEGs between each two lines that were unique for a developmental stage were greater than those that were common during all stages. Functional analysis revealed that DEGs across the entire developmental process were primarily involved in positive cell proliferation, growth, cell differentiation, and developmental processes. Genes involved in muscle regulation, muscle construction, and muscle cell differentiation were upregulated in the faster-growing breed compared to the slower-growing breed. DEGs including myosin heavy chain 15 ( MYH15 ), myozenin 2 ( MYOZ2 ), myosin-binding protein C ( MYBPC3 ), insulin-like growth factor 2 ( IGF2 ), apoptosis regulator ( BCL-2 ), AP-1 transcription factor subunit ( JUN ), and AP-1 transcription factor subunit ( FOS ) directly regulated muscle growth or were in the center of the protein–protein interaction network. Pathways, including the extracellular matrix (ECM)-receptor interaction, mitogen-activated protein kinase (MAPK) signaling pathway, and focal adhesion, were the most enriched DEGs between lines or within lines under different developmental stages. Conclusions: Genes involved in muscle construction and cell differentiation were differentially expressed among the three breeds.